Niat Mencari Ilmu Kitab Ta’lim Muta’alim Pasal 2 - Anisa Fitriana; Siti Hanifah Al Maratus Solehah; Martoyo Martoyo (Jurnal Budi Pekerti Agama Islam, 2024)
This research discusses intentions when seeking knowledge, where in seeking knowledge a person is obliged to intend, because intention is a condition for receiving knowledge and getting the blessing of knowledge, for this reason one is required to know the procedure for having good intentions and good intentions, namely intending to seek Allah's approval. Almighty Allah, intend for the happiness of the hereafter, fight ignorance in oneself and the ignorant (increase knowledge and provide benefits to oneself and society), develop and preserve Islam, be grateful for the blessings of the mind and body, and do not intend to get praise from humans, the pleasures of the world , or to get praise and closeness from leaders and so on. This research is a type of library research which takes references from books, journals and other sources that are relevant to the topic being studied.